The Effect of Sharia Marketing Strategy and Member Value toward Member Satisfactionat Ksu BMT Al-Muhajirin Toili Banggai Central Sulawesi - Lilit Biati; Risnawati Risnawati (Institut Agama Islam Negeri (IAIN) Curup, 2021)
Purpose: This study aims to determine the effect of sharia marketing strategy and member value toward member satisfaction at KSU BMT Al-Muhajirin Toili Banggai, Central Sulawesi. The objects of this research were members of the BMT with a population of 1000 members, and the samples taken were 30 members. This study aims to determine the extent of the influence of Islamic Marketing Strategy and Member Value on Member Satisfaction at KSU BMT Al-Muhajirin Toili Banggai Central Sulawesi simultaneously and partially.Design/Method/Approach: This study used quantitative analysis methods with multiple linear regression tests with hypothesis testing with the help of SPSS 23.0.Findings: The results of this study are: 1) Sharia marketing strategy (X1) significantly has an effect on customer satisfaction (Y); 2) The value of members (X2) significantly has no effect on customer satisfaction (Y); 3) Sharia marketing strategy (X1) and member value (X2) has a significant effect on member satisfaction (Y) at KSU BMT Al-Muhajirin Toili Banggai, Central Sulawesi simultaneously.Originality/Values: Therefore, the research conclusions are: 1) Sharia marketing strategy (X1) of KSU BMT Al-Muhajirin Toili Banggai Central Sulawesi is one of the factors that affect the satisfaction of prospective members. The better the marketing strategy used, the more interested people will be to become members of KSU BMT Al-Muhajirin Toili Banggai, Central Sulawesi; 2) the value of members (X2) does not affect the satisfaction of the community; this is because the value given is purely from the heart of the community and there are other factors that affect the satisfaction of members; 3) The marketing strategy of sharia (X1)) and member value (X2)) are dominant variable to satisfaction of prospective members of KSU BMT Al-Muhajirin Toili Banggai, Central Sulawesi.